THE EFFECT OF BROMELAIN MICROCAPSUL FORMULATION ON LEUKOCYTE AND TNF-α LEVEL IN MALE WHITE MICE INDUCED BY H5N1 VACCINE - UMAR, SALMAN; H. S., SARAH FADHILA; ALDI, YUFRI; BADRIYYA, ELSA (International Journal of Applied Pharmaceutics, 2023)
Objective: Bromelain is a sulfhydryl proteolytic enzyme extracted from the pineapple plant (Ananas comosus. L), which has various activities, including as an immunomodulator. Microencapsulation of bromelain is a process by which a layer surrounds bromelain to produce microcapsules to increase its activity. This research intends to see the effect of bromelain microcapsule formulation on total leukocytes count, leukocyte percentage, and the levels of TNF-α in male white mice exposed to the H5N1 Vaccine. Methods: Experimental animals were divided into three groups, specifically a negative control group given Na CMC 0.5%, the comparison group given 200 mg/kgBW bromelain enzyme, and the test group given 200 mg/kgBW bromelain microcapsules for seven days orally. On the eighth day, the total amount and the percentage of leukocytes and the levels of TNF-α were counted. The data were analyzed by two-way ANOVA and Duncan’s multiple range test (p<0.05). Results: The study showed that the administration of 200 mg/kgBW bromelain microcapsule group significantly reduced total leukocyte count and increased the segmented neutrophil compared to the bromelain group (p<0.05). However, there was no significant correlation between the two groups in reducing monocyte, lymphocyte, eosinophil, and TNF-α levels (p>0.05). Conclusion: It can be concluded that providing bromelain microcapsules can reduce the total amount of leukocytes and increase the segmented neutrophil in male white mice exposed to the H5N1 Vaccine.